2017
DOI: 10.12944/crnfsj.5.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Listeria Monocytogenes in Tomato Juice at 5 and 30°C Storage

Abstract: Listeria monocytogenes is a food-borne pathogen and has been associated with a variety of food products including fruits and vegetables, which are important for a healthy human diet. L. monocytogenes survives and grows at low temperatures and thus it can be multiplied to dangerous levels in a product which is kept at refrigeration temperatures. This work examines the ability of L. monocytogenes to survive, in a product of high consumption frequency, such as tomato juice, in correlation to storage temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In general, L. monocytogenes in fruit juices is expected survive longer at refrigeration temperatures compare to room temperature similar to E. coli and Salmonella. However, the population of L. monocytogenes decreased up to 2 logs in tomato juice held at 5 and 30°C after 12 days of storage (Diakogiannis et al, 2017). Limited effect of temperature difference on the survival of L. monocytogenes in tomato juice is probably due to the higher pH of tomato juice above 4.0.…”
Section: Discussionmentioning
confidence: 93%
“…In general, L. monocytogenes in fruit juices is expected survive longer at refrigeration temperatures compare to room temperature similar to E. coli and Salmonella. However, the population of L. monocytogenes decreased up to 2 logs in tomato juice held at 5 and 30°C after 12 days of storage (Diakogiannis et al, 2017). Limited effect of temperature difference on the survival of L. monocytogenes in tomato juice is probably due to the higher pH of tomato juice above 4.0.…”
Section: Discussionmentioning
confidence: 93%
“…In turn, avocado juice (pH 6.2) supported growth of these bacteria at both temperatures [40]. Significant number of Listeria monocytogenes suspended in tomato juice survived during storage at 5°C and 30°C for 12 days; however counts of those bacteria slightly decreased in refrigerated temperature [41]. Oyarzábal et al (2003) showed that Escherichia coli O157:H7 , Listeria monocytogenes , and Salmonella were recoverable through 12 weeks of storage at -23°C in apple, orange, pineapple, and white grape juice concentrates (pH 3.6-3.7) and banana puree (pH 5.5).…”
Section: Resultsmentioning
confidence: 99%
“…15 Studies have been performed over a wide range of temperatures that includes deep freezing, frozen and refrigeration in buffered saline, culture broths and food-based substrates with constituents that could afford protection to the culture. 16,12,[17][18][19] As the consumer focus is on microbial food safety, use of multiple barriers to prevent potential health hazards arising out of food associated L. monocytogenes and other Listeria spp., there have been a few studies on the quantitative data that could be used to estimate the relative impact of factors that interact to influence growth behavior of Listeria spp. The temperatures encountered during food processing do affect the survival / growth of bacterial cultures.…”
Section: Introductionmentioning
confidence: 99%